Identification and theoretical study of the regioselectivity of the synthesis reaction of an α-heterocyclic α-amino ester - El Mesky, Mohammed; Zgueni, Hicham; Jabha, Mohamed; Youssefi, Youssef; Amri, Nabil; Azdouz, M’barek; Oubair, Ahmad; Chebabe, Driss; Azrour, Mohamed; Mabrouk, El Houssine (Eclética Química, 2024)
The interest of amino acids no longer needs to be demonstrated, given the involvement of these compounds in various fields, both as basic elements of peptide and protein structures and as independent entities. We report the regioselective synthesis of an N-protected α,α-diamino carboxylic ester derived from glycine. Our synthetic strategy is based first on the preparation of methyl 2-azido-2-benzamidoacetate and then on the N-alkylation reaction between the latter and the 1H-1,2,4-triazole-3-amine with three methods. The theoretical study by the DFT method and Marvinsketch software explains well the reaction's regioselectivity and good compatibility between the experimental and computational results. The products synthesized during this strategy are identified and characterized by spectral analysis: mass spectrometry, 1H NMR and 13C NMR.